The Influence Of Learning Method And Gender On The Learning Outcomes Of Students At Aisyiyah Bustanul Athfal Kindergarten In Semarang City - Mufnaetty - (Universitas Muhammadiyah Semarang, 2016)
Abstract. Observation on gender related activities showed some differences. Some experts argue that those differences occur due to genetic factors and different parenting method since they was born. Therefore those differences also influenced by their learning process such as playing and storytelling method during kindergarten ages. The aim of this study was to determine whether the teaching methods and gender will alter the learning outcome of students in kindergarten. Population of this study was students in kindergarten (TK ABA) Indraprasta 01 Sub District of West Semarang and TK ABA 04 Wonodri Village District of South Semarang 2005/2006 academic year. The total population was taken as a sample unit by using cluster sampling method. The test and documentation was used to collect the data. The data than were test by using the non parametric one sample Kolmogoroft-sminov of Normality test. Two-wayanalysisof variance was used to determine the effect of learning methods and gender on learning outcomes. T-Test was used to determine differences among groups and its interactions. Results of the study were indicated that students who were learned by playing and storytelling methods did not show any differences. Learning outcome on both men and women showed no differences. Furthermore learning methods and gender have no interactive effects as well on learning outcomes.